A Híradó és Dokumentumfilm Stúdióban készült filmek
The series includes textual records such as films synopses, dialogue lists, production plans, screenplays, background and research materials for films, viewers' letters; and photo prints of stand photos and promotional photos, and documents submitted to censorship authorities pertaining to films titled “Aurél Bernáth” (Bernáth Aurél); “Sunday in Budapest” (Budapesti varásnap); “On the Crane” (A darun); “Counter Arguments” (Ellenérvek); “Late Requiem” (Kései rekviem); Faulty Circle (Hibás kör); The Fixer ( a John Frankenheimer film); “That's What a War is Like” (Ilyen a háború); “Drinking Habits” (Ivási szokások) “Shop Window” (Kirakat); “Letters to Lottery Winners” (Levelek az öttalálatosokhoz); “Worker and Technology” (Munkás és technika); “Stations” (Stációk). The series also includes film scripts of Schiffer produced for the Newsreel and Documentary Film Studio between 1970 and 1975. Accruals not expected